Plasma DNA and RNA differentially impact coagulation during abdominal sepsis - an explorative study - Schneck, Emmanuel; Lichtenstern, Christoph; Weigand, Markus A.; Uhle, Florian (Journal of surgical research, 2017)
Background: Cell-free DNA (cfDNA) and extracellular RNA (exRNA) are both suspected to activate coagulation cascades in sepsis. Therefore, our study investigated the influence of plasmatic nucleic acids on coagulation in septic patients in comparison to patients after major abdominal surgery. Materials and methods: A total of 15 patients with sepsis, 10 postoperative patients, and 10 healthy volunteers were included in this longitudinal study. Blood was collected at sepsis onset and after surgery respectively, as well as after 24, 72 and 168 h. Levels of cfDNA and exRNA were measured by quantitative probe-based polymerase chain reaction. In addition, thromboelastography for coagulation as well as thromboaggregometry for platelet function was conducted. Results: Both cfDNA and exRNA were elevated in patients with sepsis compared with postoperative patients and healthy volunteers. While higher exRNA levels correlated with a faster clotting time and more stable clots, cfDNA correlated with a shorter clotting time but also less fibrinolysis. In addition, higher cfDNA seems to be associated with kidney dysfunction as well as with general markers of cell damage (lactate dehydrogenase and lactate). Conclusions: Both nucleic acid species might be associated with different effects on coagulation during sepsis, with an overall procoagulatory influence. For this reason, individualized therapeutic approaches in patients suffering from coagulation-associated organ dysfunction might be feasible.
Available online 30 November 2016
Gesehen am 18.06.2018